65.7k views
6 votes
(5x^2 - 2x - 14) - (x^2 + 4x - 10)

User SpleenTea
by
4.6k points

2 Answers

6 votes

Answer:

4x^2−6x−4

Explanation:

Let's simplify step-by-step.

5x2−2x−14−(x2+4x−10)

Distribute the Negative Sign:

=5x2−2x−14+−1(x2+4x−10)

=5x2+−2x+−14+−1x2+−1(4x)+(−1)(−10)

=5x2+−2x+−14+−x2+−4x+10

Combine Like Terms:

=5x2+−2x+−14+−x2+−4x+10

=(5x2+−x2)+(−2x+−4x)+(−14+10)

=4x2+−6x+−4

User Bigtoe
by
4.3k points
1 vote

Answer:

2( x - 2)(2x + 1)

Explanation:

Dude

User Swickblade
by
4.1k points